Limited Sampling Strategy of Mycophenolic Acid in Adult Kidney Transplant Recipients: Influence of the Post‐Transplant Period and the Pharmacokinetic Profile. (27th June 2013) - Chaabane, Amel; Aouam, Karim; Ben Fredj, Nadia; Hammouda, Mouna; Chadly, Zohra; El May, Mezri; Boughattas, Naceur; Skhiri, Habib
Abstract We aimed to develop an accurate and convenient LSS for predicting MPA‐AUC0–12hours in Tunisian adult kidney transplant recipients whose immunosuppressive regimen consisted of MMF and tacrolimus combination with regards to the post‐transplant period and the pharmacokinetic profile. Each pharmacokinetic profile consisted of eight blood samples collected during the 12‐hour dosing interval. The AUC0–12hours was calculated according to the linear trapezoidal rule. The MPA concentrations at each sampling time were correlated by a linear regression analysis with the measured AUC0–12. We analyzed all the developed models for their ability to estimate the MPA‐AUC0–12hours. The best multilinear regression model for predicting the full MPA‐AUC0–12hours was found to be the combination of C1, C4, and C6. All the best correlated models and the most convenient ones were verified to be also applicable before 5 months after transplantation and thereafter. These models were also verified to be applicable for patients having or not the second peak in their pharmacokinetic profiles. For practical reasons we recommend a LSS using C0, C1, and C4 that provides a reasonable MPA‐AUC0–12hours estimation.